Scientific Communication Before and After Networked Science. - Carey, John (Information & Culture, 2013)
The appearance of the Philosophical Transactions in 1665 marked the emergence of scientific journals as the dominant mode for dissemination of research and discoveries. The journal system served numerous fundamental needs within the scientific community and encouraged a climate of increased sharing of knowledge. As the rhetoric of scientific discourse evolved over time, a highly stable format emerged to govern the research article as a genre. In the contemporary era of networked science, however, informal scientific communication is also growing in importance as researchers turn to online collaborative tools for even more rapid sharing of results and work in progress.